William R. Freudenburg, a life in social research - Maret, Susan (Bingley, U.K. : Emerald, 2013)
True to the nature of the Gedenkschrift, this commemorative publication celebrates the work of sociologist Dr. William Freudenburg, one of the founding editors of RSPPP and Dehlsen Professor, University of California, Santa Barbara. Chapters include personal reminiscences as well as research that reflect and build on Dr. Freudenburgs theories including recreancy, bureaucratic slippage, his research in environmental disasters, climate change natural resources, technological risk and Scientific Certainty Argumentation Method (SCAM). Government transparency, power and control are also among the topics discussed.
The sociological imagination personified : reflections on the life, scholarly contributions and professional accomplishments of William R. Freudenburg / Riley E. Dunlap -- Freudenburg and STARE at Wisconsin / Thomas A. Heberlein -- Learning to think about a mountain with Bill / Scott Frickel -- Power in coupled natural and human systems : the intellectual legacy of William R. Freudenburg / Thomas K. Rudel -- The double diversion of national energy in a globalized era : offshore oil, coal, and oil sand leases / Christine Shearer, Debra Davidson, Robert Gramling -- "Double diversion" and the environmental good : framing a disproportionate solution to an ecological threat as a problem for the commons / Daina Cheyenne Harvey, Andrew Varuzzo -- Equity, discourse, and action : an inflective paradigm linking planning, participation, and natural science / Ann Ruzow Holland -- Toward a better understanding of social problems and policy making : institutionalism of William R. Freudenburg / Ted I.K. Youn -- When recreancy becomes the norm : emergency response planning and the case of tar sands upgrading in the Alberta industrial heartland / Michael R. Edelstein -- "Peak farmland" : revealed truth or recreancy? / Charles Geisler, Ben Currens -- Freudenburg beyond borders : recreancy, atrophy of vigilance, bureaucratic slippage, and the tragedy of 9/11 / Susan Maret -- Breaking news : weapons of mass distraction deployed to fight scientific consensus on climatic changes / Margarita V. Alario -- Power and vulnerability : contextualizing "low risk" views of environmental and health hazards / Christine Shearer ... [et al.] -- Temporal myopia : a case of promising new technologies, the federal government, and inherent conflicts of interest / Mary B. Collins, William R. Freudenburg -- Development, inequality, and environmental quality : an analysis of competing hypotheses using local areas in the United States / Frank M. Howell, William R. Freudenburg (deceased), Gregory A. Works -- Robbing natures bank : preface / William R. Freudenburg.
Keywords: Freudenburg, William R; Social Science -- Sociology -- General; Social Science -- General; Social issues & processes; Social impact of environmental issues; Social sciences -- Research; Sociology -- Research